Wave-based active vibration control of a membrane structure. (January 2023) - Liu, Xiang; Lv, Liangliang; Peng, Fujun; Cai, Guoping
Wave-based active vibration control of a membrane structure by using the Active Sink Method is studied in this paper. Unlike the modal-based vibration control method which attempts to suppress several vibration modes that have already been excited, wave-based active controller can keep vibration modes inactive by stopping the formation of standing waves in the structure. First, the wave transfer matrix is deduced to characterize the wave transmission in the membrane structure. Then, feedforward wave control laws are derived analytically to absorb reflected waves or eliminate transmitted waves. The validity of the proposed active wave controllers is verified through numerical simulations. Simulation results show that by using the active wave controllers no standing waves will be produced in the structure, and the vibration of the membrane structure is suppressed significantly.